The effect of alkaloid composition of larkspur (Delphinium) species on the intoxication of Angus heifers. (17th February 2019) - Green, Benedict T; Gardner, Dale R; Pfister, James A; Welch, Kevin D; Bennett, Gary L; Cook, Daniel
Abstract: Cattle losses from larkspur ( Delphinium spp.) toxicity are a long-term challenge on the rangelands of western North America. In addition to animal factors that affect livestock poisonings, plant alkaloid composition (chemotype) affects the intoxication of cattle because some chemotypes are significantly more toxic. Differences in larkspur chemotype toxicity are due to the ratios of N -(methylsuccinimido) anthranoyllycoctonine (MSAL )-type alkaloids to non-MSAL-type alkaloids and the concentrations of those alkaloids in the plant material. The objective of this study was to compare the responses of 6 Angus heifers to 6 chemotypes of larkspur using a Latin square study design. These Angus heifers from the USDA-ARS, Meat Animal Research Center in Clay Center, NE, were chosen for this research because they are the most larkspur-susceptible cattle observed to date. The 6 heifers were given an oral dose of dried ground larkspur and tested for muscle weakness with an exercise test (i.e., walk time). The 6 chemotypes of larkspur had non-MSAL to MSAL-type alkaloid ratios ranging from 1.4:1 to 6:1 and were administered at an oral dose of 7.5 mg/kg MSAL-type alkaloids BW. There was a treatment effect due to larkspur chemotype ( P < 0.0001), and period effects were not significant ( P = 0.6). There were also significant correlations between the length of time walking on a dirt track at 5 to 6 km/h, and total alkaloid dose ( r = −0.92, P = 0.0045) and alkaloid ratio ( r = −0.81, P = 0.0258). Serum alkaloid concentrations at 24 h after dosing were representative of the relative abundance of the alkaloid in the plant material. Results from this work suggest that total alkaloid concentrations in combination with alkaloid ratios can be used together to accurately predict the plant risk component of larkspur poisoning to grazing cattle. Animal factors such as cattle age, breed, and sex must also be considered to comprehensively manage larkspur risk.